Adsorption of P and forms of iron in no-tillage areas in the ‘Cerrado’ biome - Pereira, Marcos Gervasio; Guareschi, Roni Fernandes; Perin, Adriano (Acta Scientiarum. Agronomy, 2014)
The objective of this study was to evaluate the forms of iron extracted as sodium dithionite-citrate-bicarbonate (Fed), acid ammonium oxalate (Feo) and sodium pyrophosphate (Fep) and the relationship between these variables and the total organic carbon content and maximum adsorption capacity of P (MACP). The areas selected for this study had been using a no-tillage system (NTS) for varying periods of time: 3 years (NTS3), 15 years (NTS15) and 20 years (NTS20). These areas were compared with an area of native ‘Cerrado’ (CE) and a pasture area planted with Brachiaria decumbens (PA). The soil of the areas studied was classified as dystrophic oxisol. In each area, samples were collected at 0–5 cm and 5–10 cm. A correlation was observed between the C content and the different forms of Fe in the areas studied. There was a significant positive correlation between the carbon content and the forms of iron (Feo, Feo/Fed and Fep) and a negative correlation with the level of Fed. The areas of CE and PA had the highest MACP, which diminished as the amount of time of NTS use increased.